Penerapan Metoda Student Center Learning pada Pelatihan Sketch up di SMKN 1 Karimun - Wati Masrul; Hendri Silva; Parlindungan Ravelino (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
The Sketch Up training at SMKN 1 Karimun aims to provide insight and skills about applications that help students improve their ability in managing three-dimensional shapes, especially for students majoring in Construction and Property Business Engineering. In the process of implementing the service, the learning system is carried out by providing material in stages using the Student Center Learning method. The SCL method is one of the most effective learning methods for students of SMKN 1 Karimun in understanding every step needed in the formation of modeling In learning the Sketch Up application, students are given basic material for modeling formation and then with the basic file in the form of auto CAD, students begin to learn every tool that has been given in the material debriefing to be applied to the Sketch Up application. With the application of the Student Center Learning method, it is hoped that SMKN 1 Karimun students can understand the Sketch Up application to the maximum.